2016
DOI: 10.1007/s00894-016-3186-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for nickel(0)/N-heterocyclic carbene-catalyzed intramolecular alkene hydroacylation: insights from a DFT study

Abstract: Density functional calculations have been applied to study and elucidate nickel(0)/N-heterocyclic carbene-catalyzed intramolecular alkene hydroacylation. The calculations showed that nickel(0)-catalyzed intramolecular alkene hydroacylation involved four potential reaction channels (I, II, III, and IV), and pathway IV was predicted to be more favorable than the other three. Two pathways, I and II, had three steps (oxidative addition, hydrogen migration, reductive elimination), and the rate-determining step was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…We also note that this addition process is exergonic and reversible. The facility of C–H oxidative addition has also been found in previous theoretical studies of hydroacylation reactions. , Following, there are four possible pathways: alkyne 1 can directly insert into Rh–H bond via 1,2- (path 1) or 2,1-insertion (path 2) modes, and the insertion pattern determines the regioselectivity. Alternatively, the alkyne can also coordinate with the rhodium center, pushing H downward from two different directions: the Ar substituent of alkyne lies on the same side of the Rh–C­(acyl) bond (path 3) or points away from it (path 4) (the free energy profiles for paths 3 and 4 see Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…We also note that this addition process is exergonic and reversible. The facility of C–H oxidative addition has also been found in previous theoretical studies of hydroacylation reactions. , Following, there are four possible pathways: alkyne 1 can directly insert into Rh–H bond via 1,2- (path 1) or 2,1-insertion (path 2) modes, and the insertion pattern determines the regioselectivity. Alternatively, the alkyne can also coordinate with the rhodium center, pushing H downward from two different directions: the Ar substituent of alkyne lies on the same side of the Rh–C­(acyl) bond (path 3) or points away from it (path 4) (the free energy profiles for paths 3 and 4 see Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…In the seminal work reported by Ogoshi and co-workers in 2012, they developed a Ni 0 /I t Bu catalysed intramolecular alkene hydroacylation reaction to access five/six-membered benzocyclic ketones 128 (Scheme 50). Mechanistic studies involving stoichiometric experiments 128 and DFT calculations 129 provide valuable insights into the plausible reaction mechanism which involves a dioxanickelacycle intermediate in the lowest energy pathway.…”
Section: Hydrofunctionalisation Of Alkenesmentioning
confidence: 99%
“…The dimer 328 was isolated in 84% yield in a separate stoichiometric experiment and was characterised with 1 H NMR and X-ray crystallography. A later DFT study 129 delved deeper into the mechanism and revealed that the facile dimerisation of 327 , which results in the formation of 328, significantly reduces the free energy required for the subsequent rate-determining β-hydride elimination step that leads to the formation of intermediate 329 . This is followed by a formal reductive elimination step, which releases the final benzocyclic ketone product and regenerates the active Ni/I t Bu species.…”
Section: Hydrofunctionalisation Of Alkenesmentioning
confidence: 99%